Pengaruh Kreasi Menghias Kaleng Bekas terhadap Perkembangan Motorik Halus Anak Usia Dini - Laranaya, Nandea Putri; Suryana, Dadan; Saridewi, Saridewi (JFACE: Journal of Family, Adult, and Early Childhood Education, 2019)
This study aims to determine how much the influence of decorating creation cans towards the student’s fine motor development of early childhood at Raudhatul Athfal Ikhlas Gunung Pangilun Padang. This study uses a quantitative approach in the form of quasy experiment. Data collection techniques used are test and data collection tools used, namely statement sheets. Then the data is processed by a comparison test (t-test). Based on the results of data analysis, the average value of fine motoric results of children in the experimental group was obtained with used can decorating creations (80.83) compared to control classes with paper cup decorating creations (73.75). Based on the calculation of the t-test, it is found that t count is greater than t table indicating that there is a significant effect on the child’s fine motor. Thus, it can be concluded that doing the decorating of used cans affects the fine motor development of early childhood in Raudhatul Athfal Ikhlas Gunung Pangilun Padang.